New species and additional data on the chewing louse genus Myrsidea (Phthiraptera: Menoponidae) from wild Neotropical Passeriformes (Aves) - Kolencik, Stanislav; Sychra, Oldrich; Papousek, Ivo; Kuabara, Kamila M.d.; Valim, Michel P.; Literak, Ivan (Zootaxa, 2018)
Twenty-four species of chewing lice of the genus Myrsidea Waterston, 1915 (Phthiraptera: Menoponidae) from Neotropical Suboscines (Passeriformes: Formicariidae, Furnariidae, Pipridae, Thamnophilidae, Tityridae, Tyrannidae) are recorded and discussed. They include: eight new species which are described and illustrated (Myrsidea capeki new species ex Chiroxiphia caudata; Myrsidea leptopogoni new species ex Leptopogon superciliaris; Myrsidea leucophthalmi new species ex Automolus leucophthalmus; Myrsidea pachyramphi new species ex Pachyramphus polychopterus; Myrsidea philydori new species ex Philydor rufum; Myrsidea pyriglenae new species ex Pyriglena leucoptera; Myrsidea scleruri new species ex Sclerurus scansor and Myrsidea zuzanae new species ex Furnarius rufus), as well as nine previously known species with additional data on intraspecific morphological variability, host associations and geographical distribution (Myrsidea barbati Price, Hellenthal & Dalgleish, 2005; Myrsidea dalgleishi Valim, Price & Johnson, 2011; Myrsidea flaviventris Price, Hellenthal & Dalgleish, 2005; Myrsidea klimesi Sychra, 2006; Myrsidea meyi Valim, Price & Johnson, 2011; Myrsidea oleaginei Price, Hellenthal & Dalgleish, 2005; Myrsidea olivacei Price, Hellenthal & Dalgleish, 2005; Myrsidea pitangi Price, Hellenthal & Dalgleish, 2005 and Myrsidea spellmani Price, Johnson & Dalgleish, 2008b). Seven further species are recorded at genus level only due to lack of adequate material. A 379 bp portion of the mitochondrial cytochrome oxidase I (COI) gene was sequenced from seven species in order to assess relative genetic divergences among Myrsidea populations.